2018
DOI: 10.1097/md.0000000000010680
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of patients with breast cancer after nipple-sparing mastectomy/skin-sparing mastectomy followed by immediate transverse rectus abdominis musculocutaneous flap reconstruction

Abstract: To evaluate the oncological outcomes of patients with breast cancer after nipple-sparing mastectomy (NSM)/skin-sparing mastectomy (SSM), followed by immediate reconstruction, as compared to conventional mastectomy (CM).SSM/NSM has been increasingly used to treat women with breast cancer who wish to preserve the overlying breast skin, but concern exist regarding its oncological safety due to the potential for residual breast tissue. We report our experience performing SSM/NSM for breast cancer treatment compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 43 publications
1
33
0
1
Order By: Relevance
“…A total of 457 publications were identified through PubMed and CENTRAL search using the keywords, of which 19 were eligible for inclusion in the final analysis (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). The PRISMA flow chart is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 457 publications were identified through PubMed and CENTRAL search using the keywords, of which 19 were eligible for inclusion in the final analysis (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). The PRISMA flow chart is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, to date, no randomized controlled data on the differences in the oncologic safety between mastectomy with breast reconstruction and without breast reconstruction or the oncologic outcomes of different reconstruction methods is available due to ethical concerns. Most existing studies based on retrospective data have documented that both IBR and AFR did not increase the risk of breast cancer recurrence [8][9][10][11][12]. However, con icting results have indicated that postmastectomy AFR has an increased risk of cancer recurrence compared with mastectomy alone [25].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, postmastectomy reconstruction options mainly include implant-based reconstruction (IBR) and autologous ap reconstruction (AFR) in the current clinical practice. Previous studies have demonstrated that breast reconstruction using either implants or autologous tissue does not increase the risk of breast cancer recurrence compared to conventional mastectomy without reconstruction [8][9][10][11][12]. However, few studies have compared breast cancer outcomes between the IBR and AFR [13].…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted by Lee et al [24] on immediate transverse rectus abdominis musculocutaneous flap reconstruction in breast cancer patients was exclusively based on oncological safety, while our study involved a comparison of TRAM flap with silicone implants. In our study we took the distance of the breast cancer tumor from the NAC as the main component.…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated the patient satisfaction level, as we know that this affects the clinical outcomes, patient retention, and medical malpractice claims. It affects the timely, efficient, and patient-centered delivery of quality healthcare; however, in the study conducted by Lee et al [24] the patient satisfaction level was not considered. Our study is also based on the INCISION prospectus, we used lateral incision in all the cases and immediate reconstruction of the breast was performed using the autologous graft.…”
Section: Discussionmentioning
confidence: 99%